Une exploitation minière du XVIe s. dans les Vosges Le filon Saint-Louis du Neuenberg (Haut-Rhin) : caractères et évolution - Ancel, Bruno (Documents d'archéologie française, 1988)
This monograph describes archaeological excavation carried out at a silver mine known to have been worked during the second half of the sixteenth century. The mine, named "The St-Louis Vein", is situated in the district of Ste-Marie-aux-Mines in the Haut-Rhin department of France. The study of the site introduces new methods to the archaeology of mining : the interdisciplinary approach adopted is a model of collaboration between archaeologist, speleologist and geologist. The project involves archival research, a survey of surface and belowground remains and the use of archaeological evidence to analyse how the mine was constructed and worked. The mineralogical, structural and climatological aspects of the site are also discussed. The study succeeds in reconstructing the life-history of an ancient mine located in one of the most historically interesting mining areas of Europe.